2022
DOI: 10.1007/s13555-022-00866-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Patient and Physician Disconnect on Satisfaction with Treatment for Atopic Dermatitis in Japan

Abstract: Introduction: Atopic dermatitis (AD) is an inflammatory disease causing severe skin itching. Data on patient-physician disconnect on treatment satisfaction in patients with AD in Japan are limited. We investigated patient-physician disconnect on treatment satisfaction in AD and if it influences treatment patterns, clinical characteristics, and patientreported outcomes (PROs). Methods: Data were drawn from the Adelphi AD Disease Specific Programme (DSP), a realworld, point-in-time survey of physicians and patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
3
0
0
Order By: Relevance
“…The trend is also similar to reports in Japan for other chronic skin conditions such as atopic dermatitis 39,41–43 and psoriasis 44,45 . For example, Wang et al reported that mean absenteeism, presenteeism, overall work impairment, and activity impairment in Japanese patients with atopic dermatitis were 2.8 ± 9.5%, 31.0 ± 23.4%, 31.6 ± 24.9%, and 34.8 ± 24.5%, respectively 43 . In our study, the respective values were 0.9 ± 2.8%, 23.9 ± 25.7%, 24.3 ± 25.8%, and 35.0 ± 29.5%.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The trend is also similar to reports in Japan for other chronic skin conditions such as atopic dermatitis 39,41–43 and psoriasis 44,45 . For example, Wang et al reported that mean absenteeism, presenteeism, overall work impairment, and activity impairment in Japanese patients with atopic dermatitis were 2.8 ± 9.5%, 31.0 ± 23.4%, 31.6 ± 24.9%, and 34.8 ± 24.5%, respectively 43 . In our study, the respective values were 0.9 ± 2.8%, 23.9 ± 25.7%, 24.3 ± 25.8%, and 35.0 ± 29.5%.…”
Section: Discussionsupporting
confidence: 84%
“…This was comparable with results found in the US. 27,28 The trend is also similar to reports in Japan for other chronic skin conditions such as atopic dermatitis 39,[41][42][43] and psoriasis. 44,45 43 In our study, the respective values were 0.9 ± 2.8%, 23.9 ± 25.7%, 24.3 ± 25.8%, and 35.0 ± 29.5%.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation